Transcription regulation in Plasmodium falciparum : functional characterisation of general transcription factor IIB - Talvik, Gertrud (Department of Molecular and Cell Biology, 2016)
Plasmodium falciparum is the causative agent of the most severe form of malaria and continues to pose challenges to international healthcare, with high mortality rates and emergence of drug-resistant strains. Plasmodium falciparum has multiple sexual and asexual lifecycle stages within its Anopheline mosquito and human hosts, accompanied by distinct morphological changes. The complex lifecycle, along with the ability to adjust rapidly to different environmental niches, is governed by highly regulated and tightly synchronised changes in stage-specific gene expression. In eukaryotes, regulation of RNA Polymerase II transcription initiation is one of the main mechanism of gene expression control. Past research has revealed the presence of crucial elements of RNA Polymerase II (RNAPII) transcription machinery in P. falciparum, however, the precise transcription initiation mechanisms in P. falciparum remain to date undescribed. Bioinformatics studies have found very little homology between human and P. falciparum transcription factors. Furthermore, because of the extreme bias toward A/T in the Plasmodium genome, TATA-box and other core promoter elements that direct transcription initiation, cannot be determined with confidence in bioinformatics studies. Functional characterisation of the key protein factors involved in transcription initiation is a first important step towards the identification of core promoter elements and could reveal currently unknown eukaryotic transcription initiation mechanisms or new anti-malarial targets. In eukaryotes, TATA-binding protein (TBP) and transcription factor IIB (TFIIB) are the key protein factors involved in the core promoter recognition and RNAPII preinitiation complex (PIC) assembly. TBP nucleates PIC assembly by binding the TATA box, thereafter the TBP-TATA complex is further stabilised by TFIIB. In addition, TFIIB has a crucial role in RNAPII recruitment and transcription start site selection and is therefore deemed indispensable in eukaryotic transcription. P. falciparum TBP is the only PIC component in P. falciparum that has been functionally characterised to date, albeit to a very limited extent. This research study reports the successful expression and purification, as well as initial characterisation of DNA-binding activity of P. falciparum TBP and TFIIB. We observe PfTBP binding at multiple locations on putative P. falciparum promoters. We further report PfTBP-independent binding activity of PfTFIIB, that has not been previously observed under the conditions and has implications for novel DNA-binding mechanisms of PfTFIIB. Furthermore, we conclusively demonstrate the formation of a PfTBP-PfTFIIB-promoter ternary complex.